KORELASI ANTARA SYARIAT ISLAM DAN PENDIDIKAN ISLAM - Badwi, Ahmad (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2014)
This article describes the problem of correlation of Islamic law with Islamic education. Discussion of the results obtained so understanding that education is guidance or conscious effort by educators / adults to physical and spiritual development of the students towards the formation of the main personality. In addition, Islamic education also aims to improve the morals and guiding toward a more perfect, so the task is to direct the process of Islamic education and educational activities on the principles of Islam in accordance with the guidance of the Quran and the Hadith of the Prophet. Therefore, Islamic education is very relevant to Islamic law by meeting the educational goals that we aspire together, namely the formation of the human person whole and perfect, so that they can feel the happiness and safety of the world and the life hereafter.